Evaluation of strategic management using SWOT-FAHP approaches in forest roads management - Can, Hakan; Enez, Korhan; Buğday, Ender (National Inquiry Services Center (NISC), 2022)
The most significant steps in the management of forests is to identify the management strategies of existing forest roads, which are basic infrastructure facilities. In the present study, managerial strategies were put forward by evaluating the strengths, weaknesses, opportunities, and threats of forest road management. To create a strategy in forest road management, sub-factors were identified for the SWOT analysis and five strategy criteria were developed by using expert opinions obtained through questionnaires. As SWOT analysis is a qualitative analysis and decision-making method, the strategy criteria were then modelled using the Buckley and Chang approaches, both of which are widely used in the fuzzy analytical hierarchy process (FAHP), to quantify the factors used to reach an analytical result in determining the effects and significance levels of the factors. A total of five strategy criteria along with 22 sub-factors that were prepared for SWOT analysis were modelled by making 170 pairwise comparisons and quantifying them with FAHP. The most significant factor identified, which was among the opportunity factors according to both approaches, was ‘Assisting in controlling forest fires’. According to the Buckley and Chang approaches, it was identified that the strategy that had the highest significance was ‘Protecting forest/ forest resources, and improving physical infrastructure’. It was found that the sub-factor group that had the highest degree of significance was ‘weaknesses’, while the lowest sub-factor group was the ‘opportunity’ factor. The study concluded that modelling qualitative analyses in the decision-making process after quantification results in more rational solutions because it allows a comparison of the factors.
Keywords: decision-making process, fuzzy logic, opportunity, weaknesses; 15. Life on land